Konseling Individual dengan Pendekatan Logoterapi untuk Meningkatkan Kepercayaan Diri pada Mahasiswa yang Mengalami Body Shaming - Islamiyati, Intan Islamiyati Intan (Jurnal Bimbingan dan Konseling Islam, 2021)
The phenomenon of body shaming is something that is considered commonplace and trivial in this day and age, body shaming is an act of commenting or issuing opinions to someone or yourself about their body. The criticism given is not constructive, but to bring down others. Research objectives: To find out how the condition of self-confidence of students who experience body shaming. To apply the logotherapy approach. To describe the results of the logotherapy approach. The study used qualitative methods with 5 respondents. The results of the study: lack of self-confidence of respondents as a result of the body-shaming treatment itself, on average the respondents feel worried and think if they get bad comments, cannot accept themselves as a whole, difficult to socialize, and pessimistic. the results of the research on average of respondents have begun to realize and do not feel worried about other people's bad comments, do not think about what people say, are not afraid to be criticized, and can accept themselves.